Community Service Strengthening Goat Livestock Group in Catur Village, Kintamani-Bangli District - I Dewa Nyoman Sudita; Yohanes Parlindungan Situmeang; I Komang Swedi; Stefanus Nahak; Ni Luh Putu Sulis Dewi Damayanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The province administration of Bali consistently promotes the formation of livestock farming communities, namely in goat farming, using housing and livestock aid initiatives. The